2009
DOI: 10.1152/japplphysiol.90809.2008
|View full text |Cite
|
Sign up to set email alerts
|

Nonselective NOS inhibition blunts the sweat response to exercise in a warm environment

Abstract: The role of nitric oxide synthase (NOS) inhibition in modulating human thermoregulatory control of sweating and cutaneous dilation was examined in 10 subjects (5 men and 5 women). Three intradermal microdialysis probes were placed in nonglabrous skin of the dorsum of the forearm. The control site was perfused with 0.9% saline, while the two remaining sites were perfused with a nonselective NOS inhibitor: 10 mM N(G)-nitro-L-arginine (L-NAME) or 10 mM N(G)-monomethyl-L-arginine (L-NMMA). Local sweat rate (SR) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
93
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(109 citation statements)
references
References 39 publications
13
93
3
Order By: Relevance
“…We tested this assumption in humans by assessing the influence of cutaneous vasodilation, induced by locally applied heat, on vastus lateralis SmO 2 and [tHb] measured at rest and during dynamic knee extension exercise. Local heating of the thigh caused marked increases in thigh skin blood flow, with the 42°C stimulus inducing a similar magnitude of vasodilation (*52-55% CVC peak ) to that previously reported in young adults after 30 min cycling at 60% peak O 2 consumption (*59% CVC peak ; [Welch et al 2009]). Cutaneous vasodilation caused small increases in resting SmO 2 (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 75%
“…We tested this assumption in humans by assessing the influence of cutaneous vasodilation, induced by locally applied heat, on vastus lateralis SmO 2 and [tHb] measured at rest and during dynamic knee extension exercise. Local heating of the thigh caused marked increases in thigh skin blood flow, with the 42°C stimulus inducing a similar magnitude of vasodilation (*52-55% CVC peak ) to that previously reported in young adults after 30 min cycling at 60% peak O 2 consumption (*59% CVC peak ; [Welch et al 2009]). Cutaneous vasodilation caused small increases in resting SmO 2 (Table 2; Fig.…”
Section: Discussionsupporting
confidence: 75%
“…Niacin can stimulate skin vasodilation (Benyó et al, 2006;Maciejewski-Lenoir et al, 2006) acting on vascular prostaglandin receptors (Cheng et al, 2006) and increase peripheral heat loss in dairy cows (Di Costanzo et al, 1997;Zimbelman et al, 2010). Nitric oxide synthase, a signaling molecule plausibly responsive to niacin, has also been shown to act on cutaneous thermoregulatory blood flow and sweat secretion in humans (Welch et al, 2009). Wrinkle et al (2012) observed a decrease in respiratory frequency of dairy cows in response to niacin supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…The active sweat glands for one region (axilla) have not been investigated, so this value was taken to be 90% of that reported in Table 1. Sources: Clark and Lhamon [60], Ogata [63], Randall [64], Thompson [65], Willis et al [66], Roberts et al [78], Sato and Dobson [85], Inoue et al [86], Kondo et al [87], Peter and Wyndham [88], Buono [89], Gibson and Shelley [90], MacKinnon [91] (with the original calculation error corrected), Collins et al, [92], Hellon and Lind [93], Silver et al [94], Ojikutu [95], Sargent and Weinman [96], Juniper and Dykman [97], Toda [98], Bar-Or et al [99], Knip [100], Knip [101], Schaefer et al [102], Catania et al [103], Behm et al [104], Inoue et al [105], Kondo et al [106], Inoue et al [107], Welch et al [108] and Madeira et al [109]. …”
Section: Reviewmentioning
confidence: 99%